STUDENTS ARE ECOLOGICAL IN SCIENCE TEACHING OPPORTUNITIES TO DEVELOP THINKING (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2024)
In the article, the form, methods and means of forming ecological thinking in the teaching of natural sciences in elementary grades, the essence of introducing concepts into the educational process, the principles of choosing materials related to the content of these educational sciences, as well as the elementary gradeForms, methods and means of forming ecological thinking in the teaching of natural sciences in students, creating concepts in the content of interdisciplinary relationships, instilling love for nature and the environment, primary education, which is considered the main link of the continuous education system educational plan of institutions, analysis of science programs in terms of content and purpose, determination of coherence between them, ie inter-discipline connections, formation of ecological thinking in the teaching of natural sciences, based on the form, methods and tools of students' education to know The main problems of the present time, such as the quality implementation of the process of improving the activity, the preservation of the nature aimed at the processes of pedagogical processes and educational environment active information exchange, are described